2013
DOI: 10.1371/journal.pone.0066006
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Invasive Neisseria meningitidis Strains Isolated in Chile during 2010–2011

Abstract: BackgroundWith the upcoming licensure of Outer Membrane Protein-based vaccines against meningococcal disease, data on disease incidence and molecular characteristic of circulating N. meningitidis strains in Latin American countries is needed. Chile is, to date, one of the few countries in the region that has performed this type of work in a comprehensive collection of disease-associated strains from two consecutive years, 2010–2011.MethodsA total of 119 N. meningitidis strains isolated from patients with invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 29 publications
2
23
0
3
Order By: Relevance
“…Currently, these serogroup C clones, and especially cc103, constitute the main cause of endemic meningococcal disease in Brazil [109]. As for Chile, during 2010-2011, Barra et al [84] did not observe changes in serogroup C incidence, reporting an average of 11.5%.…”
Section: Serogroup C Meningococcal Disease Epidemiologymentioning
confidence: 97%
See 1 more Smart Citation
“…Currently, these serogroup C clones, and especially cc103, constitute the main cause of endemic meningococcal disease in Brazil [109]. As for Chile, during 2010-2011, Barra et al [84] did not observe changes in serogroup C incidence, reporting an average of 11.5%.…”
Section: Serogroup C Meningococcal Disease Epidemiologymentioning
confidence: 97%
“…A study conducted on 6955 isolates collected in Latin America and the Caribbean region, and especially from Brazil and Chile, reported that 69% of the isolates belonged to serogroup B [83]. A recent investigation reported a slight lower percentage for serogroup B distribution: 63.6% in 2010 and 51.6% in 2011, upon a characterization conducted on a total of 119 N. meningitidis strains isolated in Chile [84]. Among the other countries of Latin America, serogroup B has been predominant in Argentina [85] since 2001 and especially during the periods 1993-1995 and 2002-2005, causing about two-third of cases of infections [86], and in Colombia as resulted by the analysis performed on 434 isolates collected between 1994 and 2006 [87].…”
Section: Latin Americamentioning
confidence: 98%
“…The emergence of CC11 strains associated with serogroup W in Africa represents an example of expansion of a successful clone. The epidemic with phenotype W:2a:P1.5,2 was identified in 2001 as being associated with the Hajj pilgrimage, with disease emerging throughout Europe, and, in the last few years, in Argentina and other countries in Latin America [65,175,176]. CC8 complex (formerly cluster A4), genetically related to CC11, was also mainly associated with serogroup C disease [122], was first identified in the Netherlands in 1961 [44] and has been a common cause of disease since 1970s [24,177,178], although in the last years strains belonging to CC8 have decreased worldwide (source: EU-IBIS).…”
Section: Clonal Complex 32 Outbreaksmentioning
confidence: 99%
“…CC41/44 has also been recognized as one of the most common causes of serogroup B meningococcal disease in several European countries, including the Czech Republic, Greece, Norway [38] and France [63], the USA [12,64] and Latin American countries, such as Chile [65]. From 2001 to 2006, meningococcal strains with antigenic profile B:P1.7-2,4:F1-5 caused an outbreak in the German city of Aachen and in three neighboring counties [66].…”
Section: Clonal Complex 41/44 Outbreaksmentioning
confidence: 99%
“…A pesar de los avances obtenidos en el manejo del paciente crítico, la EMI continua siendo un problema de salud pública, dado su amplia distribución, perfil epidémico y alta tasa de secuelas y letalidad asociada 3 . Dentro de las teorías que explican esta situación se considera la aparición y predominio del serogrupo W observada en Chile desde 2012, con una cepa del linaje hipervirulento W:P1.5,2:ST-11, la cual contiene el alelo ID 22 para el gen fHbp, que le daría la propiedad de ser hiperinvasor 4 . Este cambio epidemiológico motivó una campaña masiva de vacunación, con vacunas conjugadas tetravalentes ACWY, acorde a las aprobaciones vigentes para ese momento, la cual se enfocó en niños entre nueve meses y cuatro años de edad, desde octubre de 2012.…”
Section: Introductionunclassified